Interactive post-reading activities that work - Wahjudi, Arwijati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
The post-reading stage of a reading lesson is often confused with the clos- ing of a lesson. However, having new information from the whilst-reading stage should bring about a change such as the students would know more, or think or feel differently from before. Teachers should help students connect the new information they are now familiar with and their lives. This article re-introduces the importance of the post-reading stage and some workable, meaningful activities. Interactive ac- tivities are chosen so that students not only process their knowledge obtained from the text but also communicate this new knowledge to peers.